Ultrasonographic Evaluation of the Fetal Transverse Cerebellar Diameter (TCD) Measurement for Prediction of Gestational Age in 2nd and 3rd Trimesters of Pregnancy - Iram, Saira; Gilani, Syed Amir; Hassan, Zain-ul; Fatima, Mehreen; Bacha, Raham; Malik, Sajid Shaheen (International Journal of Applied Sciences and Biotechnology, 2018)
Prediction of gestational age based on sonographic fetal parameters is perhaps the cornerstone in modern obstetrics. The transverse cerebellar diameter serves as a reliable predictor of GA in the fetus and is a standard against which abnormalities in other fetal parameters can be compared. A variety of sonographic fetal biometric parameters can be used to assess gestational age in the second and third trimesters of pregnancy. The TCD is an additional biometric parameter against which aberrations in other fetal parameters can be compared. Objective: To assess the predictability of GA calculated by fetal TCD measured in 2nd & 3rd trimester of pregnancy on ultrasound. Methods: This was an cross-sectional study with a sample size 371 healthy, pregnant females with a normal fetus included aged 18 to 40 years, conducted in Gilani ultrasound center ferozpur road lahore. A standard 2nd and 3rd trimester ultrasound examination was done. In addition to the standard biometric parameters, the transcerebellar diameter was also measured. The collected data was subjected to statistical analysis. Results: Pearson product-moment correlation coefficient method was applied at a significance level of 1% (α = 0.01).using statistical software SPSS version 23.0. It was observed that BPD and TCD had a statistically significant, strong, linear correlation (r=0.976), GA of FL (r=0.978), LMP (r=0.976) P value (0.000) were considered significant. Conclusion: The TCD is a reliable parameter for the determination of GA in the 2nd & 3rd trimesters of pregnancy. Int. J. Appl. Sci. Biotechnol. Vol 6(4): 379-385